Effect of rosella-based kombucha tea on the lipid profile on hyperlipidemic rats (Rattus norvegicus) - Ahmad Edi Darmawan; Sunarno Sunarno; Vinsensius M Dhani; Garin F Fairuzzaki (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2018)
The purpose of this study was to determine the lipid profile of white rats (Rattus norvegicus) with high-fat feed after fermentation of rosella kombucha with various concentrations. This study used 20 white male rats (Rattus norvegicus) aged two months, with rosella kombucha treatment fermented for five days at 25oC per oral. This study used Completely Randomized Design with four treatments (for 21 days) and four replications, namely: P0 = Control, rats were only given food and drink as usual (with the same type of rat feed). P1 = 1 ml of pork oil/day for 14 days + 1.8 ml of rosella kombucha 50% in the morning and evening for seven days. P2 = 1 ml of pork oil/day for 14 days + 1.8 ml of 75% rosella kombucha morning and afternoon for seven days. P3 = 1 ml of pork oil/day for 14 days + 1.8 ml of 100% kombucha rosella morning and afternoon for seven days. The variables measured were levels of LDL (Low-Density Lipoprotein) and HDL (High-Density Lipoprotein). The data obtained were analyzed using ANOVA followed by Duncan Test with 95% confidence level using SPSS 16.0 software. The results showed that administration of rosella kombucha did not have a significant effect on LDL and HDL levels of white rats (Rattus norvegicus). Based on the results of the study, it can be concluded that the 5-day fermentation of kombucha rosella with various concentrations did not affect LDL and HDL levels.